Microextração líquido-líquido com solvente eutético profundo para a determinação de parabenos em cosméticos por fluorescência e calibração de segunda ordem - Silva, Daniella Iris de Oliveira (2024)
The use of personal care cosmetics has been increasing among the population, leading to a concomitant increase in exposure to substances that could potentially disrupt the endocrine system. Due to the immaturity of the metabolic system and the skin barrier, children have been the target of concern on the part of researchers with regard to the use of these cosmetics. In this work, parabens, which are esters widely used as preservatives in cosmetics, were quantified in commercial samples of diaper rash cream. For this purpose, a green and efficient liquid–liquid microextraction (LLME) method was accomplished using a deep eutectic solvent (DES). To improve extraction efficiency, the amount of solvent, time and ethanol content were optimized using a central composite design (CCD) on blank matrix samples spiked. The quantification was based on excitation-emission fluorescence spectroscopy, combined with parallel factor analysis (PARAFAC) decomposition, which proved be an advantageous tool to solve the overlap of uncalibrated constituents in the complex matrix. The PARAFAC modeling strategy provided satisfactory results within a linear range response of 100–1,300 ng g-1, with limit of detection (LOD) equal to 23 ng g-1. A validation set, with various proportions of methyl, ethyl, propyl, and butyl paraben standards, was used to validate the calibration model, resulting in root mean square error (RMSE) and relative error of prediction (REP) values of 32 ng g-1 and 4.5%, respectively. Moreover, acceptable root mean square error of prediction (RMSEP) and REP values (105 ng g-1 and 15%, respectively) were obtained, when a set of blank matrix samples spiked was applied. The proposed method was successfully applied to quantify total paraben content in commercial samples of diaper rash cream, yielding recoveries ranging from 83% to 125%. The method proved to be fast, sensitive, accurate, and eco-friendly, as it significantly reduced the consumption of organic solvents. Furthermore, it could serve as an alternative for the determination of preservatives in complex cosmetic samples.